Attack surface - Doctorow, Cory (Tor, 2020)
"Most days, Masha Maximow was sure she'd chosen the winning side. In her day job as a counterterrorism wizard for an transnational cybersecurity firm, she made the hacks that allowed repressive regimes to spy on dissidents, and manipulate their every move. The perks were fantastic, and the pay was obscene. Just for fun, and to piss off her masters, Masha sometimes used her mad skills to help those same troublemakers evade detection, if their cause was just. It was a dangerous game and a hell of a rush. But seriously self-destructive. And unsustainable. When her targets were strangers in faraway police states, it was easy to compartmentalize, to ignore the collateral damage of murder, rape, and torture. But when it hits close to home, and the hacks and exploits she's devised are directed at her friends and family--including boy wonder Marcus Yallow, her old crush and archrival, and his entourage of naïve idealists--Masha realizes she has to choose. And whatever choice she makes, someone is going to get hurt.:--